Peranan Pendidikan Dan Pelatihan Terhadap Produktivitas Kerja Pegawai Badan Pusat Statistik Provinsi Sulawesi Tenggara - Sunariani, Ni Made Suci; Justawan, Justawan; Purwati, Ninik Endang (Universitas Halu Oleo, 2020)
The purpose of this study was to determine the role of education and training on the work productivity of employees at the Badan Pusat Statistik Provinsi Sulawesi Tenggara. This is to determine the role of employee work productivity in the Badan Pusat Statistik Provinsi Sulawesi Tenggara. Data collection techniques that the authors use in this study are interviews, documentation studies, and observations. The analysis techniques that I use in this research are data collection, data reduction, data presentation, conclusion and verification. Based on the results of the study, it is known that education and training have been carried out at the office of the Central Statistics Agency of Southeast Sulawesi Province and education and training have shown a very important role in increasing employee productivity, but there are still those who think that education and training play a less role because the material provided in education and training It is different from the main tasks and functions in the office and education and training are held in separate locations, this causes ineffective time and the material provided is theoretical and practical value is lacking, so there is a lack of conformity between material needs and actual conditions. The work productivity of employees at the Central Statistics Agency of Southeast Sulawesi Province is said to be very good. Work productivity is said to be very good because in its implementation, activities are carried out based on the ability, morale of an employee and work productivity is said to be poor because employees still need work guidance from the organization.